Stereoselective synthesis of cyclohexanes via an iridium catalyzed (5 + 1) annulation strategy - Akhtar, WM; Armstrong, RJ; Frost, JR; Stevenson, NG; Donohoe, TJ (American Chemical Society, 2018)
An iridium catalyzed method for the synthesis of functionalized cyclohexanes from methyl ketones and 1,5-diols is described. This process operates by two sequential hydrogen borrowing reactions, providing direct access to multisubstituted cyclic products with high levels of stereocontrol. This methodology represents a novel (5 + 1) strategy for the stereoselective construction of the cyclohexane core.